Issues Of Enhancing The Role And Importance Of Tax Mechanisms In The Efficient Use Of Water Resources - Sodiq Boymurotov (Open Academia, 2025)
This article analyzes the current state of water resource use in our country and the measures taken for its economical and efficient use, as well as their effectiveness, examines the importance of applying tax mechanisms in the efficient use of water resources, and provides proposals and recommendations for the effective use of water in the future
Keywords: water resources; methods of efficient water use; groundwater